2016
DOI: 10.5051/jpis.2016.46.6.396
|View full text |Cite
|
Sign up to set email alerts
|

Association between dental implants in the posterior region and traumatic occlusion in the adjacent premolars: a long-term follow-up clinical and radiographic analysis

Abstract: PurposeThe aim of this retrospective study was to determine the association between dental implants in the posterior region and traumatic occlusion in the adjacent premolars, using data collected during from 2002 to 2015.MethodsTraumatic occlusion in the adjacent premolars was assessed by examining clinical parameters (bleeding on probing, probing pocket depth, fremitus, and tooth mobility) and radiographic parameters (loss of supporting bone and widening of the periodontal ligament space) over a mean follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
1
14
0
4
Order By: Relevance
“…These results are comparable to a previous report 12 , and may be mechanistically explained by recent findings reported by Lee et al 35 , that evaluated the relation between posterior dental implants and development of traumatic occlusion in the adjacent premolar teeth in 283 patients who had received 347 implants placed in the posterior region. In that cohort of patients 35 it was found that the incidence of traumatic occlusion in the adjacent premolars increased significantly when the implants were placed in the maxillary region, in the case of splinted implants, and when implants were located in the opposing occlusion. They concluded that "the risk of traumatic occlusion in the adjacent premolars increased when splinted implants were placed in the maxillary molar region and when the teeth opposing an implant also contained implants" 35 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are comparable to a previous report 12 , and may be mechanistically explained by recent findings reported by Lee et al 35 , that evaluated the relation between posterior dental implants and development of traumatic occlusion in the adjacent premolar teeth in 283 patients who had received 347 implants placed in the posterior region. In that cohort of patients 35 it was found that the incidence of traumatic occlusion in the adjacent premolars increased significantly when the implants were placed in the maxillary region, in the case of splinted implants, and when implants were located in the opposing occlusion. They concluded that "the risk of traumatic occlusion in the adjacent premolars increased when splinted implants were placed in the maxillary molar region and when the teeth opposing an implant also contained implants" 35 .…”
Section: Discussionsupporting
confidence: 92%
“…In that cohort of patients 35 it was found that the incidence of traumatic occlusion in the adjacent premolars increased significantly when the implants were placed in the maxillary region, in the case of splinted implants, and when implants were located in the opposing occlusion. They concluded that "the risk of traumatic occlusion in the adjacent premolars increased when splinted implants were placed in the maxillary molar region and when the teeth opposing an implant also contained implants" 35 .…”
Section: Discussionmentioning
confidence: 95%
“…Agliardi, Romeo, Panigatti, de Araújo Nobre and Maló (2017); Malo, de Araujo Nobre, Guedes and Almeida (2017); Niedermaier et al (2017); Zanolla et al (2016); Lee, Kweon, Choi and Kim (2016); Esposito et al (2016); Cavalli et al (2016); Zhang, Shi, Gu and Lai (2016); Imburgia and Del Fabbro (2015); Ata-Ali et al (2015); Tealdo et al (2014); Pettersson and Sennerby (2015); Ravald, Dahlgren, Teiwik and Gröndahl (2013); Kim et al (2013) Lambrecht, Filippi, Künzel and Schiel (2003); Davis, Packer and Watson (2003); Weng et al (2003); Attard and Zarb (2003); Brosky, Korioth and Hodges (2003); Naert et al (2002); Fortin, Sullivan and Rangert (2002); Wyatt and Zarb (2002); Attard and Zarb (2002); Zarb and Zarb (2002); Ferrigno, Laureti, Fanali and Grippaudo (2002); Sullivan, Sherwood and Porter (2001); Ekfeldt et al (2001); Hellem et al (2001); Merickse-Stern, Aerni, Geering and Buser (2001); Allen, McMillan and Walshaw (2001); Vajdovich and Fazekas (1999); Noack, Willer and Hoffmann (1999); Schliephake, Schmelzeisen, Husstedt and Schmidt-Wondera (1999); Chaushu and Schwartz-Arad (1999); Makkonen et al (1997); Zarb and Schmitt (1993) Same pool of patients of other article Cavalli, Corbella, Taschieri and Francetti (2015); Fischer, Stenberg, Hedin and Sennerby (2008) TA B L E 2 Study and patient characteristics of the included studies (partial prostheses) Kusakari, & Miyakawa, 1998;…”
mentioning
confidence: 99%
“…[56789] Moreover, patients with periodontitis have a higher implant-bone loss and biological complications. [404142] This issue was even discussed in the House of Lords, which indicates how serious a problem it is with conclusions that the placement of implants in patients with periodontal disease is not a treatment that should be performed without full periodontal assessment and stabilization of periodontal disease first,[43] which clearly denies the possibility of immediate implant placement in such cases not to mention functional immediate loading. On the other hand, there are also studies showing no correlation between the history of periodontal disease and the implant survival rate,[111213] but all of them concerned intra-osseous rough surface implants.…”
Section: Discussionmentioning
confidence: 99%